2016
DOI: 10.14710/medstat.9.1.51-61
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kecelakaan Lalu Lintas Di Kota Semarang Menggunakan Model Log Linier

Abstract: Traffic accident is an event in the unanticipated and unintended involve vehicles with or without other road users, resulting in losses and/or loss of property. According Polrestabes Semarang number of traffic accidents decreased in 2014 compared to 2013, but the figure is still considered high. Therefore we need an analysis of traffic accident cases, in this case using a log linear models. Log linear models used to analyze the relationship between the response variables that are categories that make up the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As for research [12], it was found that the most important factor causing accidents on Jalan Raya Cilegon was the human factor as much as 96 % of the total accident cases. In research [13] using the k-means clustering method in Semarang City, it was found that the main factor causing accidents was the driver with an average percentage of 96.57 % who was identified as the highest cause of traffic accidents in all clusters. The factors that cause accidents are vehicle drivers who are not careful in controlling their vehicles, careless drivers in driving vehicles and physical health of drivers who are less than optimal when driving on the highway which results in 183 accidents or 79.91 % [14], as well as in research [15] found that the driver factor was the main cause of accidents, namely 196 incidents (66.89 %) with the driver's lack of anticipation being the biggest cause of accidents, namely 142 incidents (72.45 %).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…As for research [12], it was found that the most important factor causing accidents on Jalan Raya Cilegon was the human factor as much as 96 % of the total accident cases. In research [13] using the k-means clustering method in Semarang City, it was found that the main factor causing accidents was the driver with an average percentage of 96.57 % who was identified as the highest cause of traffic accidents in all clusters. The factors that cause accidents are vehicle drivers who are not careful in controlling their vehicles, careless drivers in driving vehicles and physical health of drivers who are less than optimal when driving on the highway which results in 183 accidents or 79.91 % [14], as well as in research [15] found that the driver factor was the main cause of accidents, namely 196 incidents (66.89 %) with the driver's lack of anticipation being the biggest cause of accidents, namely 142 incidents (72.45 %).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Population growth that has not been followed by the growth of cities has resulted in increased traffic congestion (Wilandari, et al 2016). While traffic systems are nearing saturation, the increasing density of traffic is affecting the energy, space and time spent in transport will differ considerably from one type to the other, according to the number and density of people within the city (Ajeng and Gim 2018) Transportation has become a basic need for humans to carry out daily activities (Parmar, et al 2020).…”
Section: Introductionmentioning
confidence: 99%